Universal Efimov physics in three- and four-body collisions - Wang, Yujun (Kansas State University, 2010)
The Efimov effect plays a central role in few-body systems at ultracold temperature and has thus accelerated a lot of studies on its manifestation in the collisional stability of the quantum degenerate gases. Near broad Feshbach resonances, Efimov physics has been studied both theoretically and experimentally through the zero-energy scattering observables. We have extended the theoretical studies of Efimov physics to a much broader extent. In particular, we have investigated the three-body Efimov physics near narrow Feshbach resonances and have also identified the Efimov features beyond the zero temperature limit. We have found, near a narrow Feshbach resonance, the non-trivial contribution from both of the resonance width and the short-range physics to the three-body recombination and vibrational dimer relaxation. Remarkably, the collisional stability of the Feshbach molecules are found to be opposite to that near the broad resonances: an increased stability for molecules made by bosons and a decreased stability for those made by fermions. The universal physics observed near the narrow Feshbach resonances is further found not to be limited to the zero temperature observables. We have found that the general features of Efimov physics and those pertaining to a narrow resonance are manifested in different energy ranges above zero temperature. This opens the opportunity to observe Efimov physics by changing the collisional energy while keeping the atomic interaction fixed. The landscape of the universal Efimov physics is thus delineated in both of the interaction and the energy domain. We have also investigated Efimov physics in heteronuclear four-body systems where the complexity can be reduced by approximations. In particular, we have proposed ways for controllable production of the Efimov tri-atomic molecules by three-body or four-body recombinations involving four atoms. We have also confirmed the existence of four-body Efimov effect in a system of three heavy particles and one light particle, which has resolved a decade-long controversy on this topic. Finally, we have studied the collisional properties of four identical bosons in 1D, which is important to the experiments on the quantum gases confined in the 1D optical lattices.
Keywords: Efimov effect; few-body scattering; ultracold collisions; three-body recombination; vibrational relaxation; Feshbach resonance; Physics, Atomic (0748); Physics, General (0605); Physics, Molecular (0609)